Diagnostic imagingComparative analysis of imaging examinations of the thoracic cage in neonates. Defining indications for cat scanning - Sraga, Wojciech; Głowacki, Jan; Kluczewska, Ewa; Myga-Porosiło, Jolanta; Legaszewski, Tomasz; Czarnecki, Łukasz; Król, Katarzyna; Kozioł, Łukasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
An X-ray of the thoracic cage is a fundamental examination in children with disorders of various origin. Despite the constantly decreasing role of classic radiology in imaging diagnostics, the X-ray photograph still remains the only method available in practice for imaging lung pathologies in neonates. The aim of the work is to define the indications for performing CAT scanning of the thoracic cage in children in the neonatal period on the basis of our own material. We analysed a group of neonates referred for thoracic cage CAT scanning. Out of 10 people examined, 8 were boys, and 2 were girls. Respiratory disorders or the presence of auscultatory phenomena were an indication for making an X-ray in neonates in whom a CAT scan of the thoracic cage was done. All neonates from the examined group had an X-ray only as a result of above-mentioned indications. On the basis of a classic X-ray photograph, it was not possible to differentiate the flaccidity of the diaphragm with diaphragmatic hernia; the suspicion of presence of patent emphysema ventricle also needed to be confirmed. In one neonate, X-ray gave the image of an enlarged cone of the heart, and in the subsequent one, the image of persistent atelectasis of the right lower lobe. On the basis of the centre’s experience, we may draw the conclusions that the basic indication for performing CAT scan examination in neonates is the suspicion of anatomical irregularity mentioned in the paper.